Managing cow's milk protein allergy during the 2022 formula shortage: decision-making among pediatric healthcare providers - Oliveros, Lea V.; Brown, Jerry M.; Fabbrini, Abigail L.; Farrar, Andrew A.; Lamos, Luke; Florio, Jared; Beacker, Jesse; Baran, Jessica V.; Wilsey, Michael J. (Frontiers in Allergy, 2024)
Introduction Cow's milk protein allergy (CMPA) affects 2%-7% of infants and is managed with hypoallergenic formulas. The 2022 recalls of infant formulas due to factors including contamination led to specialty formula shortages, highlighting CMPA management challenges. Understanding healthcare providers' (HCPs) decision-making in transitioning to alternative formulas during shortages is crucial. Limited attention has been given to how pediatric physicians make these choices. Methods This study utilized US HCPs' de-identified survey data to assess driving factors when switching extensively hydrolyzed formulas during shortages. Results 104 eligible HCPs participated, including general pediatrics, pediatric allergy/immunology, and pediatric gastroenterology specialists. Safety, tolerability, and efficacy were identified as top factors for switching formulas. Formula 1 was considered well-tolerated, patient-accepted, and safe by all HCPs. Most expressed strong belief in Formula 1's safety and effectiveness. Discussion Findings inform CMPA management during shortages, offering guidance to HCPs for suitable formula selection and enhanced infant care.